2007
DOI: 10.1523/jneurosci.2849-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Central μ-Opioid Receptor Availability in Fibromyalgia

Abstract: The underlying neurophysiology of acute pain is fairly well characterized, whereas the central mechanisms operative in chronic pain states are less well understood. Fibromyalgia (FM), a common chronic pain condition characterized by widespread pain, is thought to originate largely from altered central neurotransmission. We compare a sample of 17 FM patients and 17 age-and sex-matched healthy controls, using -opioid receptor (MOR) positron emission tomography. We demonstrate that FM patients display reduced MOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
282
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(307 citation statements)
references
References 43 publications
21
282
0
4
Order By: Relevance
“…In support of this interpretation are findings in healthy subjects demonstrating that reward responsiveness is correlated with magnitude of opioid analgesia and predicts neural activity in the nucleus accumbens (Wanigasekera et al, 2012). Previous studies have shown that PCP have abnormal opioid systems (Harris et al, 2007) and in the clinic, these patients frequently show reduced response to opioids (Manchikanti et al, 2011). During chronification of pain, changes in the opioid and dopamine systems are accompanied by changes in neuronal activity and connectivity in an animal models of neuropathic pain (Chang et al, 2014), consistent with cross-sectional and longitudinal studies in humans with chronic pain (Baliki et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…In support of this interpretation are findings in healthy subjects demonstrating that reward responsiveness is correlated with magnitude of opioid analgesia and predicts neural activity in the nucleus accumbens (Wanigasekera et al, 2012). Previous studies have shown that PCP have abnormal opioid systems (Harris et al, 2007) and in the clinic, these patients frequently show reduced response to opioids (Manchikanti et al, 2011). During chronification of pain, changes in the opioid and dopamine systems are accompanied by changes in neuronal activity and connectivity in an animal models of neuropathic pain (Chang et al, 2014), consistent with cross-sectional and longitudinal studies in humans with chronic pain (Baliki et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Participant inclusion and exclusion criteria have been reported previously (5). All participants met the American College of Rheumatology 1990 criteria for the diagnosis of FM (10) and had a disease duration of at least 1 year.…”
Section: Participantsmentioning
confidence: 99%
“…Clinical evidence has also shown that opioids are ineffective in suppressing pain in fibromyalgia patients (Clauw, 2014). One of the underlying mechanisms could be attributed to reduced availability of opioid receptors in the brain (Harris et al, 2007), possibly owing to excess amounts of endogenous opioids in the cerebral spinal fluid of fibromyalgia patients (Baraniuk et al, 2004). The reduced sensitivity to morphine in the ICS model may be related to functional deficits in the descending serotonergic activity (Ohara et al, 1991;Omiya et al, 2000;Nishiyori et al, 2010), which is consistent with biochemical evidence in clinical samples (Clauw, 2009).…”
Section: Discussionmentioning
confidence: 57%